Pemberdayaan Masyarakat Melalui Pemanfaatan Pelepah Kelapa Sawit Menjadi Vermikompos untuk Mendukung Implementasi ISPO pada Perkebunan Kelapa Sawit Rakyat - Nasrul, Besri; lubis, Nursiani; Umami, Irwin Mirza; Yunandra, Yunandra; Handoko, Tito; Prakasa, Rizqy Ridho; Abdurrahman, Rezi (Unri Conference Series: Community Engagement, 2024)
The community of Sialang Sakti predominantly works as oil palm farmers. Oil palm cultivation produces biomass, one of which is palm fronds. If palm fronds are not managed properly, they can lead to detrimental effects. Piles of palm fronds can become breeding grounds for pests and diseases that may disrupt surrounding palm plants. The biomass from palm fronds can be processed into vermicompost, but this is not widely known among oil palm farmers. Therefore, it is necessary to conduct socialization regarding the processing of palm fronds into vermicompost. The socialization with the community and Gapoktan Manunggal Sakti took place at the Gapoktan Manunggal Sakti warehouse in Sialang Sakti Village, Siak Regency, Riau Province. By utilizing palm frond biomass, the community was taught how to make vermicompost, supporting sustainable farming practices and biomass utilization. This activity involved community members and Gapoktan Manunggal Sakti, using materials such as palm frond biomass, Lumbricus rubellus worms, cow manure, and sawdust. The outcome of this activity is that participants can identify potential resources, such as palm fronds and other organic waste, to process into vermicompost, which can enhance soil quality and crop productivity. It is hoped that with this training, the people of Sialang Sakti Village can adopt the use of more environmentally friendly organic fertilizers for sustainable agriculture.